A review of suspected cases of driving under the influence of drugs (DUID) involved in traffic accidents in Istanbul (Turkey) - GÜLHAN, REZZAN (ELSEVIER SCI LTD, 2013)
Nowadays traffic accidents, which have high mortality and morbidity, are an important public health problem. The association between the use of alcohol and/or drugs by drivers and the increased risk of traffic accidents with a high risk of death and injury has been well described in the literature. This study aimed to review the incidence of cases of driving under the influence of drugs (DUID) among all cases of driving under the influence (DUI) of alcohol and/or other drugs involved in traffic accidents and to evaluate the type of the psychoactive drugs (with or without alcohol) detected in blood samples in Istanbul and its surrounding area. This study is the first investigation on the subject of DUID cases in Turkey. The reports of the Istanbul Toxicology Department of the Council of Forensic Medicine (Turkey) on suspected DUID cases involved in traffic accidents between 1 July 2010 and 30 June 2011 were retrospectively reviewed for alcohol and/or drug use. Alcohol analysis was requested in 4274 suspected DUI cases, whereas drug along with alcohol analysis was requested in only 91. The rate of suspected DUID cases (n = 91) among the suspected DUI cases (n = 4274) was only 2.1% and in this study, we evaluated only the DUID cases in detail. Alcohol was present in 44% of suspected DUID cases. Psychoactive drugs were present in 15.4% of cases. The incidence among 46 confirmed DUID cases was found to be 17.4% for cannabis, 8.7% for benzodiazepines, 4.3% for barbiturates, 4.3% for antidepressants, 2.2% for cocaine and 2.2% for amphetamines. Although there is a zero-tolerance approach for DUID in the Turkish regulations, it is not well recognised and not inspected by police and legal authorities who are responsible for taking measures in traffic accidents and for routine traffic controls in Turkey. It is concluded that psychoactive drugs should be checked as well as alcohol in all traffic accident cases and roadside controls. (c) 2013 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: Traffic accidents; Drugs; Alcohol; Roadside tests; Turkish traffic regulations; Zero tolerance; FATALLY INJURED DRIVERS; MOTOR-VEHICLE DRIVERS; ORAL FLUID; IMPAIRED DRIVERS; CLINICAL IMPAIRMENT; ALCOHOL; PREVALENCE; CRASHES; BLOOD; RISK